DIAGNOSIS AND TREATMENT OF NEUROLOGICAL DISORDERS IN CHILDREN AND ADOLESCENTS USING ADVANCED IT TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The current study addresses the application of the latest information technologies and AI in assisting doctors in detecting and treating different cases of neurological disorders in children and teens efficiently and in time. It should be noted that different diseases must be revealed in time because they occur in children who face developmental issues, memory problems, motor problems, speech problems, and problems with attention. However, the latest technology has ensured that there are different computerized programs capable of checking magnetic resonance imaging and electroencephalogram data, besides monitoring the child wearing special sensors, alerting healthcare providers about any unusual events in real time. Apart from that, there are robotic assistive devices for rehab, VR technology tools, and telemedicine technology being increasingly used to ensure that the process of therapy becomes more convenient even for patients staying in remote locations with no access to large hospitals and healthcare centers whatsoever. The final section highlights the importance of AI technology development in pediatric neurology in the coming years.